Administration of Epley maneuver and stretching exercise in Benign Paroxysmal Positional Vertigo: a Case Report - Dwiky Yudhistira; Rahayu, Umi Budi; Ismadi (Physiotherapy and Physical Rehabilitation Journal, 2023)
Benign paroxysmal positional vertigo (BPPV) is a disease that is often encountered by everyone, including the elderly, characterized by dizziness and a sudden spinning sensation when doing positioning movements that can interfere with daily activities. Treatment of BPPV can be given the intervention of the Epley maneuver which is considered capable of reducing the sensation of spinning in BPPV but there has been no research in overcoming the secondary problem of BPPV, namely stiffness in the neck muscles. Giving stretching exercises to the neck area is considered capable of reducing pain, as well as improving neck function and quality of life. Purpose: to determine the effectiveness in reducing the sensation of spinning, neck muscle stiffness, and increasing functional ability in BPPV. Methods: a study using the case report method in a 50-year-old male patient diagnosed with left BPPV 6 months ago. The patient complains of a headache accompanied by a feeling of spinning and lightheadedness as well as muscle stiffness in the neck. Examination of the dix Hallpike maneuver in the patient was positive. Patients were given physiotherapy interventions in the form of Epley maneuvers and stretching exercises. Results: decreased dizziness and spinning sensation at the fifth meeting and stiffness of the neck muscles which were evaluated using the Numeric Rating Scale (NRS) and a 50% reduction at the third meeting which was evaluated using the Dizziness Handicap Inventory (DHI). Conclusion: there is effectiveness in reducing the sensation of spinning, neck muscle stiffness, and increasing functional ability in BPPV.